Success factors of MSMEs in Colombia - Castro-Silva, Hugo Fernando; Rodríguez-Fonseca, Fernando; Martínez-Chaparro, Yamith Alfonso (Clío América, 2019)
The importance of the micro-, small-, and medium-sized enterprises (MSMEs) sector in the economic and social development of a country is increasingly evident. Despite the promotion of MSMEs, the startup failure rates during the first years of operation are high. This empirical and descriptive study aims to provide a clearer understanding of the influencing factors of the success of startups, including those favored with seed capital from the national government, according to the perception of the owners/managers of these companies. The methodological design of the research contemplates a systematic literature review and two stages that incorporate quantitative and qualitative approaches. The results indicate that the relationship among finance and business networks, strategic planning, product and service innovation, supply chain management, and financing decisions significantly influence the enterprise success beyond the first two years of operation. The main contribution of this work is that it is one of the few that focuses on the entrepreneur’s direct perceptions and not on aggregate economic data.